ASSISTANCE OF BRAND REGISTRATION AT SATE ASIH RESTAURANT AS AN EFFORT TO PROTECT LEGAL PROPERTY - Nabila Sari; Tantimin Tantimin (ConCEPt - Conference on Community Engagement Project, 2022)
In Intellectual Property Rights (IPR), the brand is a symbol in the form of a logo, name, and even color as a differentiator and identification mark in the world of trade in goods and services. The role of the brand, in this case, is to maintain healthy trade competition. Therefore the brand is important for trade protection. Protection of a brand will be obtained if a trademark has been registered at the Directorate General of Intellectual Property (DJKI). So with that, it is necessary to have legal protection for marks where this arrangement is based on Law No. 20 of 2016 on Trademarks and Geographical Indications. With the issuance of regulations on trademarks, it is expected to provide legal protection for registered trademarks. Sate Asih Restaurant is the pioneer of the first Sate and Goat Curry in Batam, which was founded in 1994. However, it is known that Sate Asih has not registered its brand with DJKI. So, through this scientific research, the author seeks to assist in the registration of Sate Asih's trademark. The purpose of this research is to help Sate Asih to avoid the emergence of brand disputes. The research methods used in this study are methodology empirical legal research, in which the authors use primary data such as observation and direct interviews, assisted by secondary data in the form of library research. The result of registering a mark belonging to Sate Asih is in the form of a receipt for a trademark registration application.